Voltammetric Analysis of Ni2+ Ions Concentration inWatt’s Electrolytic Bath - Modarres-Tehrani, Z.; Sadi, A.; Mofidi, J. (Asian Journal of Chemistry, 2010)
The present results prove that Ni/Ni2+ system has an irreversible behaviour, Epc = –1.01 volt, in electrolytic formula as Watt's bath. It is possible to measure the Ni2+ ions concentration by CV, DPP and ASV voltammetric methods. Our investigations show that DPP method is the most convenient, because it is much faster than the volumetric and gravimetric methods. In com parison with spectroscopic methods, DPP is more selective, because inorganic impurities have less interference with Ni2+ peak potential. Finally, DPP is more sensitive to CV, because residual current is minimized and also faster than ASV, because DPP dose not need preelectrolysis.